Investimentos e ciclos: uma abordagem kaleckiana a partir da experiência de Minas Gerais - Beltrão, José Afonso; Lemos, Maurício Borges; Locatelli, Ronaldo Lamounier (Nova Economia, 2013)
Investimentos e ciclos: uma abordagem kaleckiana a partir da experiência de Minas Gerais